Statistic analysis of the influence shot peening parameters on the capacity of single lap adhesive joints from aluminim alloy 2024 - Władysław Zielecki; Ewelina Guźla; Magdalena Bucior; Łukasz Bąk (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
The thesis presents the results of investigations on the impact of shot peening parameters on the capacity of single lap adhesive joints from aluminium alloy 2024. Shot peening increased the capacity of joints by 3,6-20,3. What is more, the statistical analysis showed that in the assumed area variability of shot peening parameters: bali diameter, pressure and time does not significantly affect the capacity of adhesive joints from aluminium 2024.This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)